PeVDE, a violaxanthin de-epoxidase gene from moso bamboo, confers photoprotection ability in transgenic Arabidopsis under high light - Lou, Yongfeng; Sun, Huayu; Zhu, Chenglei; Yang, Kebin; Li, Xueping; Gao, Zhimin (Frontiers in Plant Science, 2022)
Plants employ an array of photoprotection mechanisms to alleviate the harmful effects of high light intensity. The violaxanthin cycle, which is associated with non-photochemical quenching (NPQ), involves violaxanthin de-epoxidase (VDE) and zeaxanthin epoxidase (ZEP) and is one of the most rapid and efficient mechanisms protecting plants under high light intensity. Woody bamboo is a class of economically and ecologically important evergreen grass species widely distributed in tropical and subtropical areas. However, the function of VDE in bamboo has not yet been elucidated. In this study, we found that high light intensity increased NPQ and stimulated the de-epoxidation of violaxanthin cycle components in moso bamboo (Phyllostachys edulis), whereas samples treated with the VDE inhibitor (dithiothreitol) exhibited lower NPQ capacity, suggesting that violaxanthin cycle plays an important role in the photoprotection of bamboo. Further analysis showed that not only high light intensity but also extreme temperatures (4°C and 42°C) and drought stress up-regulated the expression of PeVDE in bamboo leaves, indicating that PeVDE is induced by multiple abiotic stresses. Overexpression of PeVDE under the control of the CaMV 35S promoter in Arabidopsis mutant npq1 mutant could rescue its NPQ, indicating that PeVDE functions in dissipating the excess absorbed light energy as thermal energy in bamboo. Moreover, compared with wild-type (Col-0) plants, the transgenic plants overexpressing PeVDE displayed enhanced photoprotection ability, higher NPQ capacity, slower decline in the maximum quantum yield of photosystem II (Fv/Fm) under high light intensity, and faster recovery under optimal conditions. These results suggest that PeVDE positively regulates the response to high light intensity in bamboo plants growing in the natural environment, which could improve their photoprotection ability through the violaxanthin cycle and NPQ.